2021
DOI: 10.1186/s13054-021-03706-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline beta-blocker use on inotrope response and clinical outcomes in cardiogenic shock: a subgroup analysis of the DOREMI trial

Abstract: Background Cardiogenic shock (CS) is associated with significant morbidity and mortality. The impact of beta-blocker (BB) use on patients who develop CS remains unknown. We sought to evaluate the clinical outcomes and hemodynamic response profiles in patients treated with BB in the 24 h prior to the development of CS. Methods Patients with CS enrolled in the DObutamine compaREd to MIlrinone trial were analyzed. The primary outcome was a composite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
(18 reference statements)
2
20
0
1
Order By: Relevance
“… 17 , 18 , 19 , 20 , 21 As such, whether LC may be an appropriate treatment target in CS has not yet been established. In a substudy of the recently published DOREMI (Dobutamine Compared to Milrinone in the Treatment of Cardiogenic Shock) trial, we sought to confirm that LC is directly associated with survival in patients with CS and therefore may be a reasonable therapeutic target for clinicians and surrogate end points for researchers 8 , 22 (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
“… 17 , 18 , 19 , 20 , 21 As such, whether LC may be an appropriate treatment target in CS has not yet been established. In a substudy of the recently published DOREMI (Dobutamine Compared to Milrinone in the Treatment of Cardiogenic Shock) trial, we sought to confirm that LC is directly associated with survival in patients with CS and therefore may be a reasonable therapeutic target for clinicians and surrogate end points for researchers 8 , 22 (Figure 1 ).…”
Section: Figurementioning
confidence: 99%
“…Lastly, as a beta-adrenergic agonist, concern has been raised about the efficacy of dobutamine with beta-blocker therapy on board. A secondary analysis of CAPITAL DOREMI trial ∗∗ found no difference in outcomes between dobutamine and milrinone among patients treated with beta-blocker in the 24 h preceding inotrope initiation [35 ▪▪ ]. In fact, the beta-blocker cohort demonstrated fewer resuscitated cardiac arrests and deaths, with a trend toward fewer ventricular arrhythmias.…”
Section: Dobutaminementioning
confidence: 99%
“…Where two intervention arms were established (mean arterial pressure ≥70 mmHg per 36 h vs. mean arterial pressure ≤70 mmHg per 36 h) Primary outcomes (all-cause mortality, resuscitated cardiac arrest, need for cardiac transplantation, stroke or initiation of renal therapy) were more frequent in the group with low mean arterial pressure (67.6% vs. 42.2%). In patients with cardiogenic shock under treatment with Milrinone or Dobutamine, low mean arterial pressure values are associated with worse outcomes Di Santo et al [ 35 ] To evaluate clinical and hemodynamic outcomes in the use of beta-blockers in patients with cardiogenic shock under treatment with Dobutamine or Milrinone Subgroup analysis of the DOREMI clinical trial. 192 patients were included, and primary outcomes (all-cause mortality, resuscitated cardiac arrest, need for cardiac transplantation, stroke or initiation of renal therapy, among others) were evaluated 93 patients received beta-blockers.…”
Section: Physiological and Pathophysiological Considerations Of Cardi...mentioning
confidence: 99%
“…During the literature review, 4 randomized clinical trials were found that met the inclusion criteria [ 12 , [34] , [35] , [36] ], highlighting the most recent published one [ 12 ].…”
Section: Available Evidence On Milrinone Vs Dobutamine As Inotropic S...mentioning
confidence: 99%